Gut microbiota in alcohol-related liver disease: pathophysiology and gut-brain cross talk - Zhu, Lin; Wang, Yixuan; Pan, Calvin Q.; Xing, Huichun (Frontiers in Pharmacology, 2023)
Alcohol liver disease (ALD) from excessive alcohol intake has a unique gut microbiota profile.The disease progression-free survival in ALD patients has been associated with the degree of gut dysbiosis. The vicious cycles between gut dysbiosis and the disease progression in ALD including: an increase of acetaldehyde production and bile acid secretion, impaired gut barrier, enrichment of circulating microbiota, toxicities of microbiota metabolites, a cascade of pro-inflammatory chemokines or cytokines, and augmentation in the generation of reactive oxygen species. The aforementioned pathophysiology process plays an important role in different disease stages with a spectrum of alcohol hepatitis, ALD cirrhosis, neurological dysfunction, and hepatocellular carcinoma. This review aims to illustrate the pathophysiology of gut microbiota and clarify the gutbrain crosstalk in ALD, which may provide the opportunity of identifying target points for future therapeutic intervention in ALD.